Pengaruh shred injuries for basketball terhadap power tungkai - Robby Agnie Tri Subrata; Prisca Widiawati; Muhammad Putra Ramadan (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
This study was conducted to determine the effect of injury prevention program training on the cooling strength of students of SMA Negeri 8 Malang who are members of the basketball extracurricular. This study is an experimental study, which was conducted for 18 meetings with 2 meetings to take pre-test and post-test values. The design of this study used a one-group pre-test and post-test design. The population studied was 24 students consisting of 12 boys and girls at SMA Negeri 8 Malang City. The population in this study were all basketball athlete students who participated in DBL. The sample was selected using the total sampling method. The test instrument used was the MD jump test. Data analysis was carried out using the t-test, the results of the analysis with the t-test on the paired sample test showed that the t count with a sig value in the male gender (p value <a = 0.015 showed a significant difference between the pre-test and post-test (P Value <a = 0.031) women. Thus, the hypothesis H0 can be rejected and H1 is accepted. From these results it can be stated that the muscle injury prevention program has an effect on muscle power fitness in muscle power health injury increases muscle strength spasms.